Analisis Etika Bisnis Terhadap Lingkungan Kerja di BMT BUS Singgahan Tuban - Wahyuni Wahyuni (Journal of Islamic Banking, 2020)
This study aims to clearly illustrate the islamic business ethics of the work environment in Baitul Maal wat Tamwil, as well as the role of the work environment in Baitul Maal wat Tamwil Bus Singgahan-Tuban. The analysis of the research was conducted using the method of date collection techniques, which were used in the study, namely: Obsevation method is “a thechnique carried out by conducting careful observations and recording systematically”, the questionnaire method is a research tool in the form of a list of questions to obtain information from respondents. And interview method is a “Dialogue conducted by the interviewver to obtain information from the interviewee” The result showed that there was s significant influence between islamic bussines ethics on the work environment at Baitul Maal wat Tamwil Bus Singgahan-Tuban, namely to create a conductive, safe and comfortable working atmosphere. BMT Bus singgahan emphaszed and monitored good communication between others respect the opinions of other employees, both superiors and subordinates, advising and reminding each other, in addition to instilling a sense of kinship that is intertwined between superiors with employees and with fellow employees, as well as helping each other (Ta'awun) and maintaining Silaturahim ropes, so as to create a relationship a harmonious work environment and the role of the work environment is to develop employee competence. As has been explained that Islam encourages training (training) for employees with the aim of developing employee competencies and technical abilities in carrying out their work responsibilities. This can be seen with the Training provided by BMT BUS Singgahn-Tuban to new and old employees. Keywords: Islamic business ethics, working environment conditions, the role of the work environment